A New Insight Into the Underlying Adaptive Strategies of Euryhaline Marine Fish to Low Salinity Environment: Through Cholesterol Nutrition to Regulate Physiological Responses - Bao, Yangguang; Shen, Yuedong; Li, Xuejiao; Wu, Zhaoxun; Jiao, Lefei; Li, Jing; Zhou, Qicun; Jin, Min (Frontiers in Nutrition, 2022)
Salinity is an important environmental factor that can affect the metabolism of aquatic organisms, while cholesterol can influence cellular membrane fluidity which are vital in adaption to salinity changes. Hence, a 4-week feeding trial was conducted to evaluate the effects of water salinity (normal, 23 psu and low, 5 psu) and three dietary cholesterol levels (CH0.16, 0.16%, CH1.0, 1.0% and CH1.6, 1.6%) on osmoregulation, cholesterol metabolism, fatty acid composition, long-chain polyunsaturated fatty acid (LC-PUFA) biosynthesis, oxidative stress (OS) and endoplasmic reticulum stress (ERS) of the euryhaline fish black seabream (Acanthopagrus schlegelii). Results indicated that in low salinity, fish fed with CH1.0 diet improved ion reabsorption and osmoregulation by increased Na+ concentration in serum as well as expression levels of osmoregulation related gene expression levels in gill. Both dietary cholesterol level and water salinity significantly affected most of cholesterol metabolic parameters in serum and tissues, and the results showed that low salinity promoted cholesterol synthesis but inhibited cholesterol catabolism. Besides, at low salinity, hepatic expression levels of LC-PUFA biosynthesis genes were up-regulated by fed dietary cholesterol supplementation with contents of LC-PUFAs including EPA and DHA being increased. Malondialdehyde (MDA) was significantly increased in low salinity environment, whereas MDA content was decreased in fish fed with dietary CH1.0 by activating related antioxidant enzyme activity and gene expression levels. A similar pattern was recorded for ERS, which stimulated expression of nuclear factor kappa B (nf-κb), triggering inflammation. Nevertheless, fish reared at low salinity and fed with dietary CH1.0 markedly alleviated ERS and down-regulated the gene expression levels of pro-inflammatory cytokines. Overall, these findings demonstrate that cholesterol as an important nutrient plays vital roles in the process of adaptation to low salinity of A. schlegelii, and provide a new insight in the underlying adaptive strategies of euryhaline marine fishes reared at low salinity.